(untitled) (Research, Society and Development, 2025)
Embryonic loss, characterized by the interruption of pregnancy in its early stages, is a recurring challenge in the reproduction of beef cattle and has a direct impact on farm productivity and economic success. This work provides a broad and accessible overview of the main strategies to reduce these losses, showing how proper nutrition, the quality and availability of water, sanitary control, animal welfare, and genetic selection are complementary factors. It emphasizes that a balanced diet, rich in minerals and vitamins, creates more favorable uterine conditions for embryonic viability. Similarly, access to clean water in sufficient quantity ensures the hydration and hormonal balance essential for the maintenance of pregnancy. Sanitary control, through vaccination and the adoption of biosafety measures, prevents diseases that could compromise embryonic development. The selection of sires and dams with higher reproductive potential, along with the adoption of management practices that respect animal welfare, also emerges as essential strategies to reduce embryonic losses and increase productive efficiency in a sustainable and responsible manner.